ANALISIS PEMANFAATAN SMARTPHONE SEBAGAI MEDIA BELAJAR DAN PENGARUHNYA TERHADAP KREATIVITAS BELAJAR MAHASISWA PENDIDIKAN EKONOMI (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research was conducted based on a phenomenon that occurs today, namely students often use smartphones, especially as a learning media. This study aims to analyze smartphones as learning media carried out by FKIP UNRI education students and also to see whether there is an effect on learning creativity. The research was conducted at the Economic Education Study Program, FKIP UNRI. This type of research is a quantitative study with a population of 344 people and a sample of 78 people taken using probability sampling techniques (random sampling) and using the Slovin formula. Data analysis used descriptive analysis and simple linear regression analysis. The results of this study indicate that the use of smartphones as a learning medium by students of economic education is good so that the use of smartphones as a learning medium can have an influence on the learning creativity of students of Economic Education FKIP UNRI as much as 24.6%.Keywords: Smartphone, Learning Media, Learning Creativity